STUDENTS' EPISTEMOLOGICAL BELIEFS IN SOLVING GEOMETRY TRANSLATION PROBLEMS - Syafruddin Kaliky; Patma Sopamena; Arya Putra (FKIP Universitas Muhammadiyah Prof. DR. HAMKA, 2022)
The 2018 PISA results show that Indonesian students' numeracy and literacy skills are poor. Epistemological beliefs, beliefs in mathematical knowledge, are one of the factors contributing to poor student literacy skills. This study analyzes epistemological beliefs in solving translation problems of Year 9 students in one of the junior high schools in Manipa Islands, Indonesia. This research employed a descriptive a qualitative approach. The subjects in this study were students who tend to meet the indicators of epistemological beliefs. Data collection techniques were observation, tests, interviews, and documentation. The results showed that students' epistemological beliefs in completing the translation met the requirements. First is being able to solve mathematical problems by taking time, where students needed time to solve the problem. This is because students are not sure that they can solve them. Second, students can solve problems that cannot be solved with simple, step-by-step procedures, where students solve problems using their rules/settlement procedures. The third is understanding essential concepts in mathematics, where students understand and work on translation problems using mathematical concepts well. Fourth, word problems are essential in mathematics, with word problems, students can improve critical thinking skill. Finally, efforts can improve mathematical abilities, where students can try to solve problems to improve their math skills. Efforts include reviewing the lesson and increasing practice questions.